Lenz‐Majewski Hyperostotic Dwarfism with Hyperphosphoserinuria from a Novel Mutation in PTDSS1 Encoding Phosphatidylserine Synthase 1. (April 2015) - Whyte, Michael P; Blythe, Amanda; McAlister, William H; Nenninger, Angela R; Bijanki, Vinieth N; Mumm, Steven
ABSTRACT: Lenz‐Majewski hyperostotic dwarfism (LMHD) is an ultra‐rare Mendelian craniotubular dysostosis that causes skeletal dysmorphism and widely distributed osteosclerosis. Biochemical and histopathological characterization of the bone disease is incomplete and nonexistent, respectively. In 2014, a publication concerning five unrelated patients with LMHD disclosed that all carried one of three heterozygous missense mutations in PTDSS1 encoding phosphatidylserine synthase 1 (PSS1). PSS1 promotes the biosynthesis of phosphatidylserine (PTDS), which is a functional constituent of lipid bilayers. In vitro, these PTDSS1 mutations were gain‐of‐function and increased PTDS production. Notably, PTDS binds calcium within matrix vesicles to engender hydroxyapatite crystal formation, and may enhance mesenchymal stem cell differentiation leading to osteogenesis. We report an infant girl with LMHD and a novel heterozygous missense mutation (c.829T>C, p.Trp277Arg) within PTDSS1 . Bone turnover markers suggested that her osteosclerosis resulted from accelerated formation with an unremarkable rate of resorption. Urinary amino acid quantitation revealed a greater than sixfold elevation of phosphoserine. Our findings affirm that PTDSS1 defects cause LMHD and support enhanced biosynthesis of PTDS in the pathogenesis of LMHD. © 2014 American Society for Bone and Mineral Research.